Early Fire Detection On Board The Kmp Trisna Dwitya Via Smoke Detector - Melinda Exanti Noka; Anugrah Nur Prasetyo; Otri Wani Sihaloho; Arleiny (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Maritime transportation plays a vital role in supporting global and domestic logistics, but the increasing shipping activity also increases the risk of fire on board. Therefore, early detection systems such as smoke detectors are crucial to support ship safety. This study aims to analyze the working system and maintenance procedures of smoke detectors on KMP Trisna Dwitya. The study used a qualitative descriptive approach with a case study design. The study population included all crew members and the smoke detector system on board, while the sample consisted of First Officers, Second Officers, Helmsmen, and Boatswain selected using purposive sampling. Data collection was conducted through interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldana through data reduction, data presentation, and conclusion drawing. The results showed that the smoke detector system works automatically through optical sensors connected to the fire alarm panel, thus providing early identification of fire indications. Maintenance is carried out routinely through inspection, cleaning, functional testing, and logbook recording in the Planned Maintenance System. The conclusion of the study shows that the smoke detector on the KMP Trisna Dwitya has functioned effectively as an early fire detection system, although maintenance consistency still needs to be improved to minimize false alarms and maintain system reliability.